2022
DOI: 10.3389/fnins.2022.863016
|View full text |Cite
|
Sign up to set email alerts
|

EEG Evidence Reveals Zolpidem-Related Alterations and Prognostic Value in Disorders of Consciousness

Abstract: Effective treatment and accurate long-term prognostication of patients with disorders of consciousness (DOC) remain pivotal clinical issues and challenges in neuroscience. Previous studies have shown that zolpidem produces paradoxical recovery and induces similar change patterns in specific electrophysiological features in some DOC (∼6%). However, whether these specific features are neural markers of responders, and how neural features evolve over time remain unclear. Here, we capitalized on static and dynamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 83 publications
(175 reference statements)
1
3
0
Order By: Relevance
“…[35] Matt Heath utilized functional MRI to demonstrate increased cortical activity in patients with brain injuries post-zolpidem administration, indicating enhanced neural network activity. A similar enhancement was detected in electroencephalograms, [36,37] suggesting that zolpidem may influence neural network connections and cerebral blood flow, thereby underscoring its potential role in boosting neural activity and functional recovery in specific brain regions.…”
Section: Discussionsupporting
confidence: 57%
“…[35] Matt Heath utilized functional MRI to demonstrate increased cortical activity in patients with brain injuries post-zolpidem administration, indicating enhanced neural network activity. A similar enhancement was detected in electroencephalograms, [36,37] suggesting that zolpidem may influence neural network connections and cerebral blood flow, thereby underscoring its potential role in boosting neural activity and functional recovery in specific brain regions.…”
Section: Discussionsupporting
confidence: 57%
“…Second, as a dynamic system, the brain presents a research gap regarding whether brain networks underlying different brain states have the same or similar prognostic utility. Previous studies have shown that brain injuries can lead to significant alterations in brain dynamic parameters (e.g., mean state duration and mean state interval [18], [24]), but they do not necessarily result in marked alterations to the EEG brain state templates (e.g., EEG topographic maps corresponding to cluster centroids [18], [24]). Research on the prognostic abilities of brain networks underlying different brain states will provide opportunities for the identification of novel biomarkers and a deeper understanding of brain dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…However, despite being a fast‐acting sleep‐promoting drug with few side effects, little attention has been paid to its hypnotic effect on stroke subjects. To the best of our knowledge, available data on the effects of zolpidem on sleep in patients with brain injury are from patients years after brain damage 25–29 . The latest data were published by Hao et al., 27 in which the authors reported zolpidem‐induced EEG spectral features in eight patients (four stroke survivors) 4.5 months after brain injury.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, available data on the effects of zolpidem on sleep in patients with brain injury are from patients years after brain damage. 25 , 26 , 27 , 28 , 29 The latest data were published by Hao et al., 27 in which the authors reported zolpidem‐induced EEG spectral features in eight patients (four stroke survivors) 4.5 months after brain injury. Thus, in both animal models and clinical trials, there is currently little data available on the effects of zolpidem on sleep characteristics and sleep efficiency in stroke victims during the subacute phase, a critical stage for reducing neuronal death and boosting brain repair.…”
Section: Introductionmentioning
confidence: 99%